Invisible Hand behind Female Reproductive Disorders: Bisphenols, Recent Evidence and Future Perspectives - Xiaoyun Wu; Yuchai Tian; Huizhen Zhu; Pengchong Xu; Jiyue Zhang; Yangcheng Hu; Xiaotong Ji; Ruifeng Yan; Huifeng Yue; Nan Sang (Toxics, 2023)
Reproductive disorders are considered a global health problem influenced by physiological, genetic, environmental, and lifestyle factors. The increased exposure to bisphenols, a chemical used in large quantities for the production of polycarbonate plastics, has raised concerns regarding health risks in humans, particularly their endocrine-disrupting effects on female reproductive health. To provide a basis for future research on environmental interference and reproductive health, we reviewed relevant studies on the exposure patterns and levels of bisphenols in environmental matrices and humans (including susceptible populations such as pregnant women and children). In addition, we focused on in vivo, in vitro, and epidemiological studies evaluating the effects of bisphenols on the female reproductive system (the uterus, ovaries, fallopian tubes, and vagina). The results indicate that bisphenols cause structural and functional damage to the female reproductive system by interfering with hormones; activating receptors; inducing oxidative stress, DNA damage, and carcinogenesis; and triggering epigenetic changes, with the damaging effects being intergenerational. Epidemiological studies support the association between bisphenols and diseases such as cancer of the female reproductive system, reproductive dysfunction, and miscarriage, which may negatively affect the establishment and maintenance of pregnancy. Altogether, this review provides a reference for assessing the adverse effects of bisphenols on female reproductive health.